Re-Thinking Bloomfield’s Concepts of Meaning: Do Meaning Really as a Weak Point in Language Study? - Cendy Lauren; Anggi Resti Rahmadani; Farni Wulandari (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
This paper aims to describe the concepts of meaning in Bloomfield’s Theory. The methodology used to gain data in this paper is a qualitative descriptive using documentation method. Sources of data consists of words, sentences, and discourses found in the book Language by Bloomfield published by Henry Holt in New York in 1933. This research collects its data in a descriptive manner by reducing data, presentation data then drawing conclusions. The results of the analysis of this study indicate that Bloomfield underlines that meaning as a weak point in language study and believed that it might well be all expressed in behaviourist terms. Bloomfield also stressed the context of the situation was a very important level of linguistic analysis aside syntax, morphology, phonology, and phonetics, all of which support to linguistic meaning. This present study also found that Bloomfield considered words to be ambiguous notions both in everyday speech and in linguistics.